HERITAGE EDUCATION-BASED SERVICE LEARNING MODEL: AN EXPERIENTIAL STUDY ON THE PORTUGUESE SHIP "FLOR DE LA MAR", MELAKA, MALAYSIA - Satriadi Satriadi; Ditya Wardana; Satya Fauziah; Andreas Ronaldo; Maya Macia Sari; Muhammad Rendy Awali (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Heritage education-based community engagement serves as an approach that integrates historical understanding, cultural values, and social responsibility through direct experiential learning at heritage sites. This Service Learning program was conducted at the Portuguese Ship “Flor De La Mar” in Melaka, Malaysia, with the aim of strengthening students' heritage literacy while supporting the museum in enriching its educational and interpretive materials. The activities included field observation, guided cultural learning, collaboration in developing basic informational content, and structured student reflections. The program enhanced students' understanding of Melaka's maritime history, multicultural exchanges, and the importance of cultural heritage preservation. Additionally, the museum benefited from improved educational communication strategies and increased use of digital media for public engagement. The program also encouraged greater involvement of local communities and young visitors in appreciating the historical significance of Flor De La Mar. Overall, this heritage education- based Service Learning initiative strengthened contextual learning, cultivated cultural awareness among students, and fostered sustainable collaboration between the university and the heritage management community.